Mexico : New Technology-Enabled Channels to Scale Up Financial Access - International Monetary Fund; World Bank (World Bank, Washington, DC, 2014)
This is a technical note for the 2011 the Financial Sector Assessment Program (FSAP) carried out in Mexico. The focus of this document is the new technology-enabled channels to scale up financial access being employed. Key issues such as a pro-inclusion policy environment and harnessing technology for financial inclusion are discussed. Issues relevant to enabling policy framework, such as new banking regulations for branchless banking, types of licenses, types of accounts, electronic transaction mechanisms, use of banking correspondents outsourcing of operations/IT platforms, as well as other regulations affecting branchless banking propositions, are also elaborated on. Segments are devoted to the market, mobile banking schemes and the consequent recommendations as well.